TRADITIONAL CUSTOMS IN KHOREZM OASIS (Web of Discoveries: Journal of Analysis and Inventions, 2024)
This article describes the rites of cradle wedding in the Khorezm oasis, its specific aspects and related transformational processes. Besides it is said that if a girl is born, amulets are sewn on the cradle, and glasses are put on, and bread, salt, and bitter stones are placed on the head of the baby in the cradle.